Relationship With Anxiety Breast Milk Expenditure In Post Partum Mothers - Ratri, Wahyu (Sekretariat Program Studi Sarjana Terapan Manajemen Informasi Kesehatan Politeknik Indonusa Surakarta., 2022)
Smoothness expenditure Breast milk is affected by a number of factor, wrong the only one psychological factor, namely anxiety. In general, postpartum mothers often experience fatigue and change mood as worry, worried to herself and worried thinking about the baby. This anxiety can affect the smoothness of expenditure Breastfeeding in post partum mothers. The aim is to determine the relationship between anxiety and smooth discharge of breast milk in post partum mothers while being treated at the Hospitals. Method use design study cross sectional. The sample consists of 91 respondents with a non-probability sampling method sampling with purposive sampling technique . Results using the Chi – Square . test but no fulfil condition and next with test Fisher Exact on level 98% significance, the value of – Value 0.001 is smaller than the significant value of 0.05. The conclusion is that there is a relationship between anxiety and the smooth flow of breast milk on Mother post partum During treated in Hospital.